Extração de óleo de gérmen de milho com o uso de CO2 em condições supercríticas e cossolventes - Marinho, Carolina Messias (2017)
Corn germ oil is commonly used for cooking, salads, margarines and animal nutrition due to the mild flavor and nutritional power in its composition. Currently, the most widely used method of corn germ oil extraction involves the use of organic solvents, which are mostly expensive, require long extraction time, and they present considerable levels of flammability and toxicity. In order to obtain the oil with better quality, greater technical and economic viability, and environmental sustainability, the supercritical extraction with the use of CO2 stands out as a clean, innovative, efficient technology with environmentally friendly extracts. The objective of the present work was the study of the extraction of corn germ oil with the use of carbon dioxide and addition of cosolvents (hexane, acetone and ethanol). In order to evaluate the influence of temperature and pressure on corn germ oil yield, experiments were carried out at temperatures of 45-85 °C, pressure of 150-250 bar and flow rate of 3 mLCO2/min for the tests conducted with supercritical CO2. For the tests with addition of cosolvents, temperature range of 40-80 °C, pressure of 250 bar, CO2 flow rate of 4 mL/min, and cosolvents flow rates of 0.01 up to 0.1 mL/min were used. The conventional extraction with the use of organic solvents ethanol, acetone and hexane was also performed for comparison purposes. The extracted oil samples were submitted to density analysis, refraction index, acidity, peroxide index, fatty acids profile and antioxidant activity. The results showed that pressure had a positive effect and temperature had a negative effect on the yield of the extraction with the use of CO2. The yield results with the addition of cosolvents were higher than the use of supercritical CO2, reaching a maximum yield of 13.81% using ethanol. In addition, the analysis of density, refractive index, acidity, peroxide and fatty acids profile did not present significant differences between the oils obtained by the conventional method, with the use of CO2 and cosolvents addiction.